Local Pocket Internet and Global Social Media Bridging the Digital Gap: Facebook and Youth Sub-Stratum in Urban India - Rangaswamy, Nimmi; Cutrell, Ed; Challagulla, Gautami; Young, Margaret (IFIP 9th International Conference on Social Implications of Computers in Developing Countries, 2013)
As Web 2.0 technologies penetrate the world and as more people are spurred to go online, the digital literacy gap shrinks yet differences persist: mainly between users who have infrastructural supports and those who do not to acess, use and persist with ICTs. Technologies in developing countries like India have found new ways to immerse and embed into the social milieu of users. Our paper offers a Developemnt 2.0 framework to investigate Facebook in India as social media with developemnt impacts on everyday day life. The focus of this paper is Facebook as appreciable and compelling new media for non-elite youth in urban India. We use our research as a springboard for understanding the ways internet technologies are continually re-defining social practices in the urban edges of developing economies. Having reached the socially disadvantaged, Facebook is transforming as a space to learn, play and connect with global digital culture. Facebook, for the non-elite youth in India, is ignited by two products: the modest feature phone and the micro pre-pay pocket internet serviced by local and global providers and mediated by the desire of young facebook users. Once ignited, we argue the mobile phone as the central, sometimes only, device for multi-media affordances priming socio-digital experiences. This research is an anthropologically informed study about low income users of the mobile [pre-pay] internet accessing facebook primarily on their [modest] phones and the possibilities of transgressing social identity, transforming self-perception, expanding social connections and life chances. Development 2.0 should examine ways in which the provision of alternative platforms of social and economic exchange can work to energize new forms of communication behaviours and social interactions conferring media entitlements for the digital-poor in the world. The key to understanding this relationship is for a more reflexive, critical and beneficial understanding of developmental benefits accruing to user engagement with Web 2.0.SNS technologies.